IMPROVING THE PROFESSIONAL ABILITY OF NURSES IN NURSING INTERVENTIONS IN HOSPITALS THROUGH EVIDENCE-BASED NURSING PRACTICE WORKSHOP - Adin Mu'afiro; Joko Suwito; Kiaonarni Ongko Waluyo; Sri Hidayati; Supriyanto Supriyanto; Hepta Nur Anugrahini (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
The evidence-based approach in Indonesia has not yet developed, including the use of research results in practice. Thus it is necessary to grow the attitude, willingness, awareness, and ability to develop EBNP or transform research results into practice so that nurses can improve the